Interconnected influences: a critical review of qualitative research on willingness to communicate in EFL classrooms - Ahmad, Nur Haziq Fikri; Abd Razak, Fatin Nabila; Hossein, Vahid Nimehchisale; Husin, Siti Husniah (Human Resources Management Academic Research Society (HRMARS), 2024)
This critical review examines qualitative studies on Willingness to Communicate (WTC) in English among English as a Foreign Language (EFL) learners, exploring the complex interplay between individual, cultural, and contextual factors. By analyzing the impact of classroom environments, teacher behaviours, and cultural norms, this study highlights how intrinsic factors like motivation, anxiety, and self-confidence influence learners' WTC. The review integrates findings from both ecological and psychological perspectives, focusing on the role of supportive educational contexts and culturally sensitive teaching approaches in fostering communication. Key insights reveal that creating inclusive, motivating, and culturally responsive learning environments enhances WTC. The study also emphasizes the importance of adopting a holistic ecological framework to account for the dynamic interactions between personal traits, classroom dynamics, and cultural backgrounds. Practical recommendations are provided for educators and policymakers to develop strategies that enhance WTC in diverse EFL settings. Furthermore, the review calls for longitudinal research to track the evolution of WTC over time, particularly across different cultural contexts.